ANALISIS WAKTU PADA PEMBANGUNAN DAM PENAHAN JALAN BINUANG KOTA BUKITTINGGI MENGGUNAKAN MICROSOFT PROJECT - Ahmad Kamal; Ishak Ishak; Deddy Kurniawan (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2022)
In the implementation of a construction project, delays are very common in the field. Acceleration is needed to overcome or minimize the delay. The acceleration efforts made will certainly have an impact on increasing the time on the project so it is necessary to analyze the time for the construction. There are many methods that can be done one of them by using the help of a computer program. The purpose of this study was to determine the time through Microsoft Project 2016 analysis. A case study was conducted on the construction of the Binuang Road Retaining Dam in Bukittinggi City, with a project implementation time of 17 weeks or 120 working days. The alternative used in this research is to analyze or review the time of the project. Furthermore, scheduling analysis is carried out through Microsoft Project 2016 so that the critical path is obtained which becomes a reference for activities to be optimized and to analyze the time that occurs after the acceleration is carried out by the Crashing Program. After analyzing the results, the same results were obtained in the Microsoft Project 2016 output. The maximum acceleration occurred in the addition of working days or the absence of holidays or 7 days faster than the normal duration of 113 days. Keywords: acceleration, Microsoft Project, Crashing Program.